Different Mechanisms for Supporting Mental Imagery and Perceptual Representations: Modulation Versus Excitation - Pace, Thomas; Koenig-Robert, Roger; Pearson, Joel (Psychological Science, 2023)
Recent research suggests imagery is functionally equivalent to a weak form of visual perception. Here we report evidence across five independent experiments on adults that perception and imagery are supported by fundamentally different mechanisms: Whereas perceptual representations are largely formed via increases in excitatory activity, imagery representations are largely supported by modulating nonimagined content. We developed two behavioral techniques that allowed us to first put the visual system into a state of adaptation and then probe the additivity of perception and imagery. If imagery drives similar excitatory visual activity to perception, pairing imagery with perceptual adapters should increase the state of adaptation. Whereas pairing weak perception with adapters increased measures of adaptation, pairing imagery reversed their effects. Further experiments demonstrated that these nonadditive effects were due to imagery weakening representations of nonimagined content. Together these data provide empirical evidence that the brain uses categorically different mechanisms to represent imagery and perception.